Alles richtig – nichts verstanden? - Amadeus Bärtsch; Lorenz Marti (CHIMIA, 2023)
This article presents ideas from our educational practice in chemistry teaching, focusing on understanding rather than just learning by heart. We recommend always asking students to justify statements, to use chemical formulae as a starting point and aid to reasoning, and to require as little factual knowledge as possible. Because tasks with calculations, formulae and reaction equations can be solved in a recipe-like manner, they should be supplemented with comprehension questions. If students describe processes with sketches at model level and formulate explanations in their own words, it becomes particularly clear whether they have understood the concept.